Evaluation of urban livability based on spatial distribution and functional radius of land uses - Hashemkhani Zolfani, Sarfaraz; Hedayatnezhad Kashi, Seyed Mostafa; Antuchevičienė, Jurgita (International Journal of Strategic Property Management, 2023)
The present research has evaluated the spatial distribution and functional radius of land uses in the central district of Tehran city using objective and subjective methods. The findings showed; Land uses have a directional pattern with random distribution and a cluster. The functional radius also indicates a lack of desirable access for residents to land uses. On the other hand, the lack of per capita confirms the results of the functional radius of the land uses. Because the district is facing a per capita shortage in all uses and functional scales. The results of subjective evaluations also showed that residents lack ease of access to land uses. Also, the optimal access to land uses from the residents’ perspectives has been contrary to the standards of urban development plans. What has been quite evident is that spatial injustice in the distribution of land uses and the presence of disparities in access to land uses have had a negative impact on the livability of the district. Our results underscore the importance of a comprehensive examination of livability based on the spatial justice of land uses. This necessitates simultaneous attention to distribution patterns, functional radii of land uses, and the involvement of residents’ perceptions of that space.